A Socio-Cultural Value Embedded in English Textbook Seventh Grade Students of Junior High School - Yanti, Sarli; Tahrun, Tahrun; Mulyadi, Mulyadi (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aimed to identify the central issues of socio-cultural values, understand how these socio-cultural values are implemented, and determine the dominance of specific socio-cultural values represented in the 7th grade English textbook titled "English for Nusantara.". The purpose of this study was to find out whether an English textbook for seventh grade students of junior high school published by Kemendikbudristek fulfilled the sociocultural value. The sociocultural aspects were analyzed based on criteria established by Purwoko (2010), with a particular emphasis on Indonesian sociocultural elements. The researchers used a descriptive qualitative research approach. The data triangulation for a socio-cultural analysis thesis using the English textbook 'English for Nusantara' was: documentation, interview, and forum group discussion. The data used in this research was written texts and visual images on the English textbook of seventh grade students of junior high school entitled “English for Nusantara." Data were gathered through document analysis of the English textbook "English for Nusantara," designed for seventh-grade students and published by Kemendikbudristek. The document analysis was conducted throughout the duration of the study. The researchers followed five steps to analyze the data: selecting the English textbook, identifying socio-cultural values, classifying these values, interpreting the socio-cultural values present in the textbook, and drawing conclusions. The results confirmed that the contents of the textbook fulfilled the socio-cultural values, particularly those relevant to Indonesian culture. The analysis was based on six sociocultural values identified by Purwoko: nomenclature, address terms, cultural information, cultural sites, socio-cultural traditions, and etiquette. Among these, nomenclature emerged as the dominant value represented in the textbook. The author effectively incorporated these socio-cultural elements, ensuring that while the textbook focused on the English language, it also preserved the socio-cultural context of the target learners' country.